Project eyeball : keeping a watch on inertia. - Au, Kheng Sheng. (2008)
By using Foucault's archaeology, this study will analyze two recent developments in Singapore that purported to give the people greater political space-the establishment of the Project Eyeball newspaper and the setting up of Speakers' Corner.